Foundation Treatment Assessment and Postconstruction Settlement Prediction of a Loess High Fill Embankment: A Case Study - Caihui Zhu; Xiaosong Zhou; Songhe Wang (Shock and Vibration)
The design of high fill embankments (HFEs) on the loess plateau requires proper foundation treatment methods and reasonable prediction of postconstruction settlement (PCS). In situ tests were carried out on a test section of the collapsible loess foundation of a high fill airport to assess the reinforcement effects of common treatment methods. Based on in situ monitored data, the spatial-temporal variations of the PCS of the HFE were investigated, with a simple empirical formula proposed for PCS prediction. The PCS increases linearly with the fill thickness, and the PCS rate varies exponentially with the fill rate. Two engineering recommendations were made to reduce differential PCS and water damage for the test site. The first is to combine the reinforcement methods to reduce PCS of the HFE, i.e., dynamic compaction for loess foundation with lower water content and gravel piles with stabilizers for that with higher water content. The second is to employ the dynamic compaction (DC), percussive compaction (PC), and vibration compaction (VC) to strengthen the fill to reach an average compaction degree above 0.93 and a water content close to the optimal.